Preparation method of core-shell rubber particles with magnetic function
The magnetic particle Fe3O4 is wrapped through emulsification and grafting technology to form rubber particles with core-shell structures, solving the problem of uneven sedimentation and dispersion of iron tetraoxide particles in the material, and achieving the bonding of magnetic functions and the improvement of material toughness.
Patent Information
- Application Number
- CN202411966409.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-12-30
AI Technical Summary
Iron tetraoxide particles have problems of settlement and uneven dispersion in adhesives and coating materials, which limits their application.
A preparation method is adopted to wrap the magnetic particle Fe3O4 through emulsification and grafting technology to form rubber particles with core-shell structure, and the particle size can be adjusted between 0.5 and 50um.
The combination of magnetic functions is achieved, which prevents brittle fracture, improves material toughness, and has the advantages of anti-sinking in dispersed in acrylate monomers, avoiding the problems of uneven dispersion and stratified settlement.
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing core-shell rubber particles with magnetic function, belonging to the technical field of polymer material preparation. Background Art
[0002] As a traditional magnetic material, ferroferric oxide (Fe3O4) has the advantages of high magnetic permeability, high wave absorption strength and simple preparation. However, it also has some disadvantages, such as easy agglomeration of particles, sedimentation and uneven dispersion when directly used in adhesives and coating materials, which limit its further application. Summary of the invention
[0003] In view of the deficiencies in the prior art, the present invention provides a method for preparing core-shell rubber particles with magnetic function. The particle size is adjustable between 0.5 and 50 μm. When applied to conventional polymer structural materials, the particles can not only prevent brittle fracture and improve material toughness, but also have the magnetic function of ferrosoferric oxide and have the advantage of anti-settling when dispersed in acrylic ester monomers.
[0004] To achieve the above objectives, the technical solutions adopted are:
[0005] The object of the present invention is to provide a method for preparing core-shell rubber particles having magnetic function, comprising the following steps:
[0006] (1) using deionized water to prepare an aqueous solution of FeCl2 and FeCl3 as an aqueous phase W11, using deionized water to prepare an aqueous solution of NaOH and a reducing agent as an aqueous phase W12, and using chloroform and dichloromethane to prepare a rubber latex as an oil phase O1; mixing the aqueous phase W11 with the oil phase O1, adding an emulsifier E1, controlling the rotation speed, temperature and time, to prepare a colostrum emulsion W11 / O1; mixing the aqueous phase W12 with the oil phase O1, adding an emulsifier E1, controlling the rotation speed, temperature and time, to prepare a colostrum emulsion W12 / O1;
[0007] (2) adding the colostrum emulsion W11 / O1 and the colostrum emulsion W12 / O1 into deionized water in which the emulsifier E2 is dispersed in advance, and heating the water to react, thereby obtaining a latex particle bundle wrapping the magnetic particle Fe3O4;
[0008] (3) adding the pre-prepared grafted acrylate monomer mixture oil phase O2 to the latex particle bundle wrapping the magnetic particle Fe3O4 in step (2), controlling the reaction temperature, and grafting acrylate monomers on the outer layer of the latex particle bundle wrapping the magnetic particle Fe3O4; wherein the preparation process of the oil phase O2 includes the following steps: dissolving the acrylate monomer and the initiator in a mixed solution of chloroform and dichloromethane;
[0009] (4) The temperature is raised to 60-100° C., and the chloroform and dichloromethane solvents are removed by condensation and reflux, and the product is filtered, washed and dried to obtain the final product.
[0010] Furthermore, in the step (1), the mass ratios of FeCl2, FeCl3 and deionized water in the aqueous phase W11 are 27-45:13-15:40-60; the mass ratios of NaOH, deionized water and reducing agent in the aqueous phase W12 are 20-45:52-79.5:0.5-3; the mass ratios of chloroform, dichloromethane and rubber latex in the oil phase O1 are 23-60:30-47:10-30; the mass ratios of the aqueous phase W11, the oil phase O1 and the emulsifier E1 are 10-40:55-89:1-5; the mass ratios of the aqueous phase W12, the oil phase O1 and the emulsifier E1 are 10-45:50-89:1-5.
[0011] The beneficial effect of adopting the above technical solution is that the role of emulsifier E1 is to make W11 and W12 stably exist in O1 and O2, and the purpose of selecting chloroform and dichloromethane for oil phase O1 is to adjust the stability of oil phase O1 in W2 according to the difference in density extractability between the two.
[0012] Furthermore, the reducing agent is at least one of N,N-dimethyl-p-toluidine, tetramethylthiourea, and aldehyde-amine condensation products; the rubber latex is at least one of natural rubber latex, epoxidized natural rubber latex, nitrile rubber latex, and acrylate emulsion; and the emulsifier E1 is at least one of sucrose fatty acid ester, polyglycerol fatty acid ester, and polyoxyethylene castor oil.
[0013] The beneficial effect of adopting the above technical solution is that the reducing agent promotes the decomposition of the initiator to generate free radicals, which trigger the grafting of acrylate monomers around the latex particles that wrap the magnetic particles.
[0014] Furthermore, in step (1), the stirring speed is 500 to 1000 rpm / min, the temperature is 20 to 30° C., and the time is 10 to 30 min.
[0015] Furthermore, the step (2) further comprises the following steps: mixing deionized water and emulsifier E2 in advance at a stirring speed of 500 to 1000 rpm / min, a temperature of 20 to 30° C., and a time of 10 to 30 min, wherein the mass ratio of deionized water to emulsifier E2 is 95-99:1-5, and is recorded as W2; the mass ratios of W11 / O1, W12 / O1, and W2 are 10-20:10-20:60-80 respectively; and the emulsifier E2 is at least one of glyceryl stearate PEG-100, Croda A165 emulsifier, ABIL CARE 85 silicone emulsifier, EG emulsifier, Prexin 721 emulsifier, and BASF A25 emulsifier.
[0016] The beneficial effect of adopting the above technical scheme is that the role of emulsifier E2 is to make W11 / O1 and W12 / O1 stably exist in W2, prevent W11 and W12 from demulsifying in O1 and O2 respectively, and at the same time, adjusting the ratio of (W11 / O1) and (W12 / O1) can regulate the content of magnetic Fe3O4 particles in the latex particles.
[0017] Furthermore, the temperature of the temperature-raising reaction in step (2) is 40 to 70° C., and the reaction time is 10 to 90 minutes.
[0018] Furthermore, the step (3) further comprises the following steps: mixing chloroform, dichloromethane, acrylate monomer and initiator in advance at a stirring speed of 500 to 1000 rpm / min, a temperature of 20 to 30°C and a time of 10 to 30 min, and recording them as oil phase O2, wherein the mass ratios of chloroform, dichloromethane, acrylate monomer and initiator in the oil phase O2 are 14-25:26-49:25-55:1-5 respectively; adding the mixed oil phase O2 dropwise to the latex particle bundle wrapping the magnetic particle Fe3O4 while stirring, the stirring speed being 500 to 1000 rpm / min, and the material temperature of the latex particle bundle wrapping the magnetic particle Fe3O4 during the addition being 30 to 60°C.
[0019] Furthermore, the mass ratio of the sum of the three W11 / O1, W12 / O1, and W2 to the oil phase O2 is 60-80:20-40; the acrylate monomer is at least one of styrene St, acrylonitrile AN, and methyl methacrylate MMA, and the initiator is at least one of benzoyl peroxide and isopropylbenzene hydroperoxide.
[0020] The beneficial effect of adopting the above technical scheme is that the purpose of this reaction step is to graft acrylate monomers on the outer layer of the latex particle bundle that wraps the magnetic particle Fe3O4. The purpose of selecting chloroform and dichloromethane for the oil phase O2 in this step is to adjust the stability of the oil phase O2 in W2 according to the difference in density extractability between the two.
[0021] Furthermore, the cleaning in step (4) is to first use anhydrous ethanol to wash the product 1 to 2 times, and then use deionized water to wash 3 to 4 times, and the drying is to dry at 80° C. for 2 hours.
[0022] The beneficial effect of adopting the above technical solution is that the purpose of using anhydrous ethanol for washing is to wash away the excess unreacted acrylate monomer in step (3).
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] The core-shell rubber particles with magnetic functions prepared by the present invention not only have a core-shell structure and can provide excellent impact strength, but also are different from the physical blending of conventional magnetic materials and polymer resins. The inorganic magnetic particles in the present invention are rubber core-shell structures that are encapsulated and formed during the emulsification grafting process, thereby avoiding many problems such as uneven dispersion and stratified sedimentation during later use or storage. DETAILED DESCRIPTION
[0025] The principles and features of the present invention are described below. The examples given are only used to explain the present invention and are not used to limit the scope of the present invention.
[0026] Example 1
[0027] The first step is to weigh FeCl2: 25.2g, FeCl3: 12.6g, deionized water: 52.2g, stir at a speed of 600rpm / min, the temperature is 25℃, and stir for 15min, record it as W11 for standby; weigh NaOH: 22.4g, deionized water: 69.5g, N,N-dimethyl-p-toluidine 0.82g, stir at a speed of 600rpm / min, the temperature is 25℃, and stir for 15min, record it as W12 for standby; weigh chloroform: 500g, dichloromethane: 300g, natural rubber latex: 200g, stir at a speed of 600rpm / min, the temperature is 25℃, and stir for 15min, record it as O1 for standby; weigh W11: 85g, O1: 490g, sucrose fatty acid ester: 12g, stir at a speed of 600rpm / min, the temperature is 25℃, and stir for 15min, record it as O1 for standby. m / min, temperature is 25℃, stir for 15min, record it as W11 / O1 for later use; weigh W12: 100g, O1: 480g, polyglycerol fatty acid ester: 12g, according to the speed of 600rpm / min, the temperature of 25℃, stir for 15min, record it as W12 / O1 for later use; second step, weigh deionized water: 3590g, glyceryl stearate PEG-100: 108g, according to the speed of 600rpm / min, the temperature of 25℃, stir for 15min, record it as W2 for later use; weigh (W11 / O1): 580g, (W12 / O1): 580g, W2: 2000g, according to the speed of 800rpm / min, the temperature of 50℃, stir for 20min, and the product is a latex particle bundle wrapped with magnetic particles Fe3O4. The third step is to weigh 200g of chloroform, 400g of dichloromethane, 360g of styrene St, and 36g of benzoyl peroxide, stir at a speed of 600rpm / min and a temperature of 25℃ for 15min, and record it as O2 for standby; take 900g of O2 and add it dropwise to the product of the second step while stirring, at a stirring speed of 800rpm / min, and the material temperature during the addition is 45℃. The product of this step is the grafting of acrylate monomers on the outer layer of the latex particle bundle wrapping the magnetic particle Fe3O4. The fourth step is to heat the product of the third step to 80℃, condense and reflux to remove the chloroform and dichloromethane solvents, and then filter the above product, and wash the product twice with anhydrous ethanol, and then wash it with deionized water for 3 times, and then dry it at 80℃ for 2h to obtain the final product.
[0028] Example 2
[0029] The first step is to weigh FeCl2: 25.8g, FeCl3: 12.0g, deionized water: 52.2g, stir at a speed of 600rpm / min, the temperature is 25℃, and stir for 15min, record it as W11 for standby; weigh NaOH: 23.9g, deionized water: 68g, tetramethylthiourea 2.2g, stir at a speed of 600rpm / min, the temperature is 25℃, and stir for 15min, record it as W12 for standby; weigh chloroform: 400g, dichloromethane: 400g, nitrile rubber emulsion: 200g, stir at a speed of 600rpm / min, the temperature is 25℃, and stir for 15min, record it as O1 for standby; weigh W11: 80g, O1: 485g, polyglycerol fatty acid ester: 12g, stir at a speed of 600rpm / min, the temperature is 25℃, stirred for 15min, recorded as W11 / O1 for later use; weigh W12: 100g, O1: 480g, polyglycerol fatty acid ester: 12g, according to the speed of 600rpm / min, the temperature of 25℃, stirred for 15min, recorded as W12 / O1 for later use; secondly, weigh deionized water: 3590g, Prexin 721 emulsifier: 108g, according to the speed of 600rpm / min, the temperature of 25℃, stirred for 15min, recorded as W2 for later use; weigh (W11 / O1): 580g, (W12 / O1): 580g, W2: 2000g, according to the speed of 800rpm / min, the temperature of 50℃, stirred for 20min, and the product was a latex particle bundle wrapped with magnetic particles Fe3O4. The third step is to weigh 200g of chloroform, 400g of dichloromethane, 360g of acrylonitrile AN, and 36g of isopropylbenzene hydroperoxide, and stir at a speed of 600rpm / min and a temperature of 25℃ for 15min, and record it as O2 for standby; take 900g of O2 and add it dropwise to the product of the second step while stirring, and the stirring speed is 800rpm / min. The material temperature during the addition is 45℃. The product of this step is the grafting of acrylic acid ester monomer on the outer layer of the latex particle bundle wrapping the magnetic particle Fe3O4. The fourth step is to heat the product of the third step to 80℃, condense and reflux to remove chloroform and dichloromethane solvents, and then filter the above product, and wash the product twice with anhydrous ethanol, and then wash it with deionized water for 3 times, and then dry it at 80℃ for 2h to obtain the final product.
[0030] Example 3
[0031] Step 1: Weigh 24 g of FeCl2, 13.8 g of FeCl3, and 52.2 g of deionized water, stir at a speed of 600 rpm / min and a temperature of 25°C for 15 min, and record it as W11 for later use; weigh 23 g of NaOH, 68.9 g of deionized water, and 0.82 g of N,N-dimethyl-p-toluidine, stir at a speed of 600 rpm / min and a temperature of 25°C for 15 min, and record it as W12 for later use; weigh 450 g of chloroform, 350 g of dichloromethane, and 200 g of acrylate emulsion, stir at a speed of 600 rpm / min and a temperature of 25°C for 15 min, and record it as O1 for later use; weigh 85 g of W11, 490 g of O1, and 12 g of polyoxyethylene castor oil, and stir at a speed of 600 rpm / min and a temperature of 25°C. m / min, temperature is 25℃, stir for 15min, record it as W11 / O1 for later use; weigh W12: 100g, O1: 480g, polyglycerol fatty acid ester: 12g, according to the speed of 600rpm / min, the temperature of 25℃, stir for 15min, record it as W12 / O1 for later use; second step, weigh deionized water: 3590g, BASF A25 emulsifier: 108g, according to the speed of 600rpm / min, the temperature of 25℃, stir for 15min, record it as W2 for later use; weigh (W11 / O1): 580g, (W12 / O1): 580g, W2: 2000g, according to the speed of 800rpm / min, the temperature of 50℃, stir for 20min, and the product is a latex particle bundle wrapped with magnetic particles Fe3O4. The third step is to weigh 180g of chloroform, 450g of dichloromethane, 360g of methyl methacrylate MMA, and 36g of benzoyl peroxide, and stir them at a speed of 600rpm / min and a temperature of 25℃ for 15min, and record them as O2 for standby; take 900g of O2 and add it dropwise to the product of the second step while stirring, at a stirring speed of 800rpm / min, and the material temperature during the addition is 45℃. The product of this step is the grafting of acrylate monomers on the outer layer of the latex particle bundle wrapping the magnetic particle Fe3O4. The fourth step is to heat the product of the third step to 80℃, condense and reflux to remove the chloroform and dichloromethane solvents, and then filter the above product, and wash the product twice with anhydrous ethanol, and then wash it with deionized water for 3 times, and then dry it at 80℃ for 2h to obtain the final product.
[0032] Comparative Example 1
[0033] Step 1: weigh 26 g of FeCl2, 15.2 g of FeCl3, and 62 g of deionized water, stir at a speed of 600 rpm / min and a temperature of 25°C for 15 min, and record it as W11 for later use; weigh 26 g of NaOH and 68.9 g of deionized water, stir at a speed of 600 rpm / min and a temperature of 25°C for 15 min, and record it as W12 for later use; weigh 200 g of chloroform and 420 g of dichloromethane, stir at a speed of 600 rpm / min and a temperature of 25°C for 15 min, and record it as O1 for later use; weigh 85 g of W11, 490 g of O1, and 12 g of polyoxyethylene castor oil, stir at a speed of 600 rpm / min and a temperature of 25°C 15min, recorded as W11 / O1 for later use; weigh W12: 100g, O1: 480g, polyglycerol fatty acid ester: 12g, according to the speed of 600rpm / min, the temperature of 25℃, stir for 15min, recorded as W12 / O1 for later use; secondly, weigh deionized water: 3590g, BASF A25 emulsifier: 120g, according to the speed of 600rpm / min, the temperature of 25℃, stir for 15min, recorded as W2 for later use; weigh (W11 / O1): 580g, (W12 / O1): 580g, W2: 2000g, according to the speed of 800rpm / min, the temperature of 50℃, stir for 20min, and the product is a latex particle bundle wrapped with magnetic particles Fe3O4. In the third step, the product of the second step is heated to 80°C, condensed and refluxed to remove chloroform and dichloromethane solvents, and then the above product is filtered, and the product is first washed twice with anhydrous ethanol, and then washed three times with deionized water, and then dried at 80°C for 2h to obtain the final product.
[0034] Comparative Example 2
[0035] Step 1: weigh 75 g of deionized water and 1.0 g of N,N-dimethyl-p-toluidine, stir for 15 min at a speed of 600 rpm / min and a temperature of 25°C, and record it as W1 for later use; weigh 450 g of chloroform, 350 g of dichloromethane, and 250 g of acrylate emulsion, stir for 15 min at a speed of 600 rpm / min and a temperature of 25°C, and record it as O1 for later use; weigh 90 g of W1, 500 g of O1, and 12 g of polyoxyethylene castor oil, and stir for 15 min at a speed of 600rpm / min, temperature is 25℃, stir for 15min, record it as W1 / O1 for later use; second step, weigh deionized water: 3590g, BASF A25 emulsifier: 120g, according to the speed of 600rpm / min, temperature is 25℃, stir for 15min, record it as W2 for later use; weigh W1 / O1: 600g, W2: 2000g, according to the speed of 800rpm / min, temperature is 50℃, stir for 20min, and the product is a latex particle bundle encapsulating the reducing agent. The third step is to weigh 170g of chloroform, 420g of dichloromethane, 360g of methyl methacrylate MMA, and 36g of benzoyl peroxide, and stir them at a speed of 60rpm / min and a temperature of 25℃ for 15min, which is recorded as O2 for standby use; 900g of O2 is added dropwise to the product of the second step while stirring, at a stirring speed of 800rpm / min, and the material temperature is 45℃ during the addition. The product of this step is the outer layer grafted acrylate monomer of the latex particle bundle. The fourth step is to heat the product of the third step to 80℃, condense and reflux to remove chloroform and dichloromethane solvents, and then filter the above product, and wash the product twice with anhydrous ethanol, and then wash it with deionized water for 3 times, and then dry it at 80℃ for 2h to obtain the final product.
[0036] Specific test verification plan:
[0037] When conducting specific experiments to verify the formula, in order to more fully compare with the Fe3O4 inorganic particles synthesized in Comparative Example 1 and the core-shell rubber particles synthesized in Comparative Example 2, commercially available Fe3O4 inorganic particles were selected as blank group 1, and commercially available Zhongyuan core-shell rubber particles M521 were selected as blank group 2. The formula is shown in Table 1:
[0038] Table 1.
[0039] raw material Blank group 1 Comparison group 1 Blank Group 2 Comparison group 2 Experimental Group 1 Experimental Group 2 Experimental Group 3 Isobornyl acrylate 80 80 80 80 80 80 80 Commercially available Fe304 inorganic particles 20 - - - - - - Comparative Example 1 Synthesis of Inorganic Particles - 20 - - - - - Commercially available Zhongyuan core-shell rubber particles M521 - - 20 - - - - Comparative Example 2 Synthesis of core-shell rubber particles - - - 20 - - - The magnetic core-shell rubber particles in Example 1 of this patent - - - - 20 - - Magnetic core-shell rubber particles in Example 2 of this patent - - - - - 20 - Magnetic core-shell rubber particles in Example 3 of this patent - - - - - - 20 total 100 100 100 100 100 100 100
[0040] The magnet adsorption and storage stability experiments were followed in sequence, and the comparative test data are shown in Table 2:
[0041] Table 2.
[0042] Experiment No. Magnet adsorption Storage stability Blank group 1 Fe304 adsorption and aggregation 12h at room temperature, Fe304 precipitation Comparison group 1 Synthetic inorganic particles adsorption aggregation 12h at room temperature, inorganic particles settle Blank Group 2 No change No sedimentation after 7 days storage at 40°C Comparison group 2 No change No sedimentation after 7 days storage at 40°C Experimental Group 1 Adsorption and aggregation of core-shell rubber particles No sedimentation after 7 days storage at 40°C Experimental Group 2 Adsorption and aggregation of core-shell rubber particles No sedimentation after 7 days storage at 40°C Experimental Group 3 Adsorption and aggregation of core-shell rubber particles No sedimentation after 7 days storage at 40°C
[0043] It can be seen from the above table that the core-shell rubber particles with magnetic function prepared by the present invention not only have magnetic function, but also are different from the physical blending of conventional magnetic materials and polymer resins. The inorganic magnetic particles in the present invention are rubber core-shell structures that are wrapped and formed during the emulsification grafting process, thereby avoiding many problems such as uneven dispersion and stratified sedimentation during later use or storage.
[0044] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing core-shell rubber particles with magnetic function, characterized in that: The following steps are involved: (1) using deionized water to prepare an aqueous solution of FeCl2 and FeCl3 as an aqueous phase W11, using deionized water to prepare an aqueous solution of NaOH and a reducing agent as an aqueous phase W12, and using chloroform and dichloromethane to prepare a rubber latex as an oil phase O1; mixing the aqueous phase W11 with the oil phase O1, adding an emulsifier E1, controlling the rotation speed, temperature and time, to prepare a colostrum emulsion W11 / O1; mixing the aqueous phase W12 with the oil phase O1, adding an emulsifier E1, controlling the rotation speed, temperature and time, to prepare a colostrum emulsion W12 / O1; (2) adding the colostrum emulsion W11 / O1 and the colostrum emulsion W12 / O1 into deionized water in which the emulsifier E2 is dispersed in advance, and heating the water to react, thereby obtaining a latex particle bundle wrapping the magnetic particle Fe3O4; (3) adding the pre-prepared grafted acrylate monomer mixture oil phase O2 to the latex particle bundle wrapping the magnetic particle Fe3O4 in step (2), controlling the reaction temperature, and grafting acrylate monomers on the outer layer of the latex particle bundle wrapping the magnetic particle Fe3O4; wherein the preparation process of the oil phase O2 includes the following steps: dissolving the acrylate monomer and the initiator in a mixed solution of chloroform and dichloromethane; (4) The temperature is raised to 60-100° C., and the chloroform and dichloromethane solvents are removed by condensation and reflux, and the product is filtered, washed and dried to obtain the final product.
2. The method for preparing core-shell rubber particles with magnetic function according to claim 1, characterized in that: In the step (1), the mass ratios of FeCl2, FeCl3 and deionized water in the aqueous phase W11 are 27-45:13-15:40-60; the mass ratios of NaOH, deionized water and reducing agent in the aqueous phase W12 are 20-45:52-79.5:0.5-3; the mass ratios of chloroform, dichloromethane and rubber latex in the oil phase O1 are 23-60:30-47:10-30; the mass ratios of the aqueous phase W11, the oil phase O1 and the emulsifier E1 are 10-40:55-89:1-5; the mass ratios of the aqueous phase W12, the oil phase O1 and the emulsifier E1 are 10-45:50-89:1-5.
3. The method for preparing core-shell rubber particles with magnetic function according to claim 1 or 2, characterized in that: The reducing agent is at least one of N,N-dimethyl-p-toluidine, tetramethylthiourea, and aldehyde-amine condensation products; the rubber latex is at least one of natural rubber latex, epoxidized natural rubber latex, nitrile rubber latex, and acrylate emulsion; and the emulsifier E1 is at least one of sucrose fatty acid ester, polyglycerol fatty acid ester, and polyoxyethylene castor oil.
4. The method for preparing core-shell rubber particles with magnetic function according to claim 1, characterized in that: The step (2) further comprises the following steps: mixing deionized water and emulsifier E2 in advance at a stirring speed of 500 to 1000 rpm / min, a temperature of 20 to 30° C., and a time of 10 to 30 min for standby use, wherein the mass ratio of deionized water to emulsifier E2 is 95-99:1-5, and is recorded as W2; the mass ratios of W11 / O1, W12 / O1, and W2 are 10-20:10-20:60-80 respectively; and the emulsifier E2 is at least one of glyceryl stearate PEG-100, Croda A165 emulsifier, ABIL CARE 85 silicone emulsifier, EG emulsifier, Prexin 721 emulsifier, and BASF A25 emulsifier.
5. The method for preparing core-shell rubber particles with magnetic function according to claim 4, characterized in that: The step (3) further comprises the following steps: mixing chloroform, dichloromethane, acrylate monomer and initiator in advance at a stirring speed of 500 to 1000 rpm / min, a temperature of 20 to 30°C and a time of 10 to 30 min for standby use and recording the mixture as oil phase O2, wherein the mass ratios of chloroform, dichloromethane, acrylate monomer and initiator in the oil phase O2 are 14-25:26-49:25-55:1-5 respectively; and dripping the mixed oil phase O2 into the latex particle bundle wrapping the magnetic particle Fe3O4 while stirring, wherein the material temperature of the latex particle bundle wrapping the magnetic particle Fe3O4 is 30 to 60°C during the dripping.
6. The method for preparing core-shell rubber particles with magnetic function according to claim 5, characterized in that: The mass ratio of the sum of the three W11 / O1, W12 / O1 and W2 to the oil phase O2 is 60-80:20-40; the acrylate monomer is at least one of styrene, acrylonitrile and methyl methacrylate; the initiator is at least one of benzoyl peroxide and isopropylbenzene hydroperoxide.
7. The method for preparing core-shell rubber particles with magnetic function according to claim 1, characterized in that: The cleaning in step (4) is to first use anhydrous ethanol to wash the product 1 to 2 times, and then use deionized water to wash it 3 to 4 times. The drying is to dry it at 80° C. for 2 hours.
Citation Information
Patent Citations
Water dispersible magnetic polymer microsphere and preparing method
CN101343370A
Preparation method of unsaturated polyester resin low shrinking agent
CN104356309A
Method for preparing high-dispersibility polystyrene magnetic microsphere
CN106478853A
Graphene-encapsulated electroactive material for use in a lithium ion electrochemical cell
CN108352511A
Polyhydroxyalkanoate-containing magnetic structure, and manufacturing method and use thereof
US20060263432A1